2021
DOI: 10.1016/j.ijid.2021.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure secondary to myocarditis after SARS-CoV-2 reinfection: a case report

Abstract: Introduction: Cardiac involvement in COVID-19 can range from mild damage to severe myocarditis. The precise mechanism by which COVID-19 causes myocardial injury is still unknown. Myocarditis following administration of COVID-19 vaccines, especially those based on mRNA, has also been described. However, no reports of heart failure following reinfection with COVID-19 in patients immunized with an inactivated vaccine have been identified. Case description : Male, 47-year-old, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…A total of 100 case reports or case series which reported cardiac complications after COVID-19 vaccination were included 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 100 case reports or case series which reported cardiac complications after COVID-19 vaccination were included 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , …”
Section: Resultsmentioning
confidence: 99%
“…A study in Brazil reported a 47-year-old African-American male patient with type 2 diabetes and a previous history of COVID-19 infection. He had heart failure as a result of myocarditis after the second dose of an inactivated COVID-19 vaccine 45 . Other studies reported no myocarditis incidence in a subject receiving inactivated COVID-19 vaccine 126 , 127 .…”
Section: Resultsmentioning
confidence: 99%